Survey of the chance of secondary salinization in the hobby gardens around Karcag - Zsembeli, József; Szűcs, Lilla (Acta Agraria Debreceniensis, 2010)
Irrigation involves the risk of secondary salinization on certain areas. The increase of the level of salty groundwater or the applicationof poor quality (salty) irrigation water can cause secondary salinization. Irrigation from drilled wells is very characteristic in the smallhobby gardens located around Karcag during the frequently droughty summers. Mainly vegetables and fruits with high water demand aregrown in these gardens, hence quite a large amount of subsurface waters are used for irrigation. Water samples were taken from 46 drilledwells located in the hobby gardens around the town of Karcag and analysed in order to survey the risk of secondary salinization. On thebase of the results of the analyses and some indexes calculated from the chemical parameters of the irrigation waters, it can be establishedthat none of the investigated wells supply water that is suitable for irrigation without improvement.